Health behaviors and tooth retention among older adults in China: findings from the 4th Chinese national oral health survey - Xiaoyan Ou; Liwei Zeng; Yixuan Zeng; Yaolin Pei; Xiujuan Zhang; Wei Wu; Shahrzad Siamdoust; Bei Wu (BMC, 2022)
Abstract Background This study aimed to examine the association between oral health behaviors and tooth retention among Chinese older adults. Methods Data were used from the 4th Chinese National Oral Health Survey, a nationally representative sample. The sample included 9054 older adults aged 55 to 74. Control variables and oral health behaviors were measured through a questionnaire interview, and the number of remaining teeth and periodontal health were obtained from an oral health examination. A chi-square test was used for univariate analysis. Multivariate Logistic regression was used to explore the association between health behaviors and the number of remaining teeth. Results The average number of remaining teeth in the sample was 24.4 ± 7.7. There was a higher proportion of older adults living in urban areas with 20 or more teeth than those living in rural areas (83.2% vs. 79.4%, P < 0.001); and a higher proportion of individuals with high education levels with 20 or more teeth compared to those with low education levels (P < 0.001). Logistic regression models showed that older adults who used toothpicks `(OR = 3.37, 95% CI 2.94-3.85), dental floss (OR = 1.93, 95% CI 1.05-3.53), toothpaste (OR = 3.89, 95% CI 3.14-4.83); and never smoked (OR = 1.43 95% CI 1.20-1.70) were more likely to retain 20 or more natural teeth; whereas older adults who had a dental visit were less likely to retain 20 or more natural teeth (OR = 0.45, 95% CI 0.39-052). Conclusion Good oral hygiene practices, never smoking, and regular dental visits focusing on prevention are significantly associated with teeth retention. It is critical to promote a healthy lifestyle and improve prevention-oriented oral health care systems.